Desafios na gestão patrimonial: investigação em uma instituição federal de ensino - Sá, Rosimere Gomes de (2024)
This study investigated the asset management of permanent movable goods in a Federal Educational Institution (FEI), from the perspective of the Integrated Risk Management Model (COSO). Using a qualitative approach, with a deductive method and a single case study, the practices and procedures adopted in asset management were analyzed, aiming to understand their contribution to the increase in unlocated assets. The participants were members of the Asset Coordination of each managing unit belonging to the researched FEI. Data collection involved document and legislative analysis, semi-structured interviews, and observations. Data analysis was conducted through Bardin's content analysis. The results integrated insights into the COSO framework, identifying gaps in the control environment, risk assessment, control activities, information and communication, and monitoring. One of the main findings of the research was the identification of the asset coordinators' lack of knowledge about which procedure to adopt when an asset is classified as unlocated. The limitations of this research included temporal restriction and an exclusive focus on asset coordinators. Future research is recommended to broaden the inclusion of participants and extend the study to other institutions, aiming to improve asset management in higher education institutions and strengthen their integrity and accountability to society.